Serum interleukin-6 concentration in patients with pemphigus (Dermatology Reports, 2024)
Pemphigus is a rare blistering autoimmune disease that damages the integumentary system and lowers the quality of life of patients. Interleukin-6 (IL-6) has been linked to the immunopathogenesis of pemphigus, according to recent research. Thus, the investigation purpose was to assess the function of IL-6 in the development and intensity of pemphigus disease. Between January 2022 and August 2022, a case-series study involving 26 patients with pemphigus vulgaris (PV), four patients with pemphigus foliaceus (PF), and 20 healthy volunteers was carried out at the Ho Chi Minh City Hospital of Dermato-Venereology. Patients with PV and PF had significantly higher serum IL-6 concentrations than healthy volunteers (p